Review: The Helsinki Atlas of the Near East in the Neo-Assyrian Period - Millard, Alan (Journal of Semitic studies, 2005)
The Helsinki Atlas of the Near East in the Neo-Assyrian Period Simo Parpola and Michael Porter , The Casco Bay Assyriological Institute and The Neo-Assyrian Text Corpus Project, Helsinki 2001. xii + 46, 33 maps, map in pocket. Price: $29.95 . ISBN: 951-45-9050-3